The Role of the Concept of the Right to Renew Islamic Legal thought - Hamah Saeed, Tahseen (Journal of University of Human Development, 2018)
In spite of all the richness that exists around the concept of the right in Islamic legal thought, it is mentioned in detail in the branches and types. Muslim scholars have discovered some types of truth that were not present in the Western jurisprudence. However, this great legal heritage lacks an integrated theory or is almost free to say Of the definition of this great concept in modern times.The researcher assumed that the question is not related to the accuracy of consideration, endurance and patience in the research, which is based on the virtue achieved by the Muslim scholars themselves.But it concerns the question of paradigm, the concept of changing the perception of all issues in a holistic manner.In other words, instead of dealing with the attempt to find out partial solutions, turn the corner and change the view.In order to renew the Islamic legal thought, we do not need to continue to solve the particles, but rather to change the direction, to replace the Paradigm, which was based on the concept of duty to the right-based Paradigm.